Psychological Distress and Problematic Mobile Phone Use Among Adolescents: The Mediating Role of Maladaptive Cognitions and the Moderating Role of Effortful Control - Liu, Ru-De; Hong, Wei; Ding, Yi; Oei, Tian Po; Zhen, Rui; Jiang, Shuyang; Liu, Jingxuan (Frontiers in Psychology, 2019)
Previous studies have documented that psychological distress is related to problematic mobile phone use (PMPU), and sporadic research has investigated the potential mechanisms underlying the association. Based on the cognitive-behavioral model of pathological Internet use (PIU), the self-control theory, and the problem-behavior theory, this study aimed to examine the mediating role of maladaptive cognitions toward mobile phones and the moderating role of effortful control between psychological distress and PMPU. Data were collected from 1,799 secondary school students (45.1% male; Mage = 14.07, SD = 1.69) using four self-reported questionnaires. The results revealed that maladaptive cognitions toward mobile phones partially mediated the relationship between psychological distress and PMPU. In addition, effortful control as a protective factor attenuated the indirect effect from psychological distress to PMPU. These findings advanced the understanding of the etiology of PMPU and the need to develop effective strategies for prevention, suggesting that schools and families should pay additional attention to students with psychological distress. Targeted interventions for integrating online and offline worlds and effortful control training programs may help to prevent adolescents from engaging in PMPU.